Determining the functional form of relationships between oil prices and macroeconomic variables: The Case of MIST Countries - Caglayan Akay, Ebru; Kangalli Uyar, Sinem Guler (International Journal of Economics and Financial Issues, 2016)
The aim of this study is to investigate that how economic conditions change when crude oil shocks occured in 1980-2013 for MIST countries. Another objective of the study is to determine accurately the functional forms of the relationships between oil prices and macroeconomic variables. For this aim, the relationships between crude oil price and macroeconomic variables were estimated by using Additive Model being a nonparametric model. In order to make comparisons, estimation results of the OLS model being parametric were also given. The F test statistics showed that relationships between crude oil price and macroeconomic variables were explained by nonparametric models better than parametric models. Teraesvirta Neural Network test (1993) shows also that oil price shocks can cause to be symmetric effects on macroeconomic variables while asymmetric effects on some macroeconomic variables. Keywords: Crude Oil Price, Macroeconomic Variables, Partial Response Functions JEL Classifications: C53, C14, Q43,Q41